Laparoscopic surgery for inguinal hernia: Current status and controversies - Bhandarkar Deepraj (Journal of Minimal Access Surgery, 2006)
Repair of inguinal hernia is one of the commonest operations performed by surgeons around the world. The treatment of this common problem has seen an evolution from the pure tissue repairs to the prosthetic repairs and in the recent past to laparoscopic repair. The fact that so many hernia repairs are practiced is a testimony to the fact that probably none is distinctly superior to the other. This review assesses the current status of surgery for repair of inguinal hernia and examines the various controversial issues surrounding the subject.